Correlation of Serum HER-2/neu Levels with Clinico-Pathological Variables and Tissue Immunohistochemistry in Breast Carcinoma / Islam Barkatullah ... [et al.] - Barkatullah, Islam; Ahmad, Syed Shamshad; Akhtar, Kafil; Mansoor, Tariq (Universiti Teknologi MARA Cawangan Selangor, 2021)
Introduction: Serum levels of HER-2/neu protein is raised in primary as well as metastatic breast cancer and decreased serum HER-2/neu concentration in patients treated with HER- 2/neu inhibitors like trastuzumab is a good prognostic indicator in metastatic cases. Aims: To evaluate the concordance of serum HER-2/neu concentration with tissue HER-2/neu immunohistochemistry and determine its relationship with various prognostic indicators like age, size of tumour, lymph node status, grade, and stage of tumour. Methods: The preoperative serum samples of 56 clinically and cytologically diagnosed cases of breast carcinoma were taken and postoperative mastectomy specimens were examined for the histologic type, lympho-vascular invasion, stage, and grade of the tumour. Immunohistochemical study of HER-2/neu expression and HER-2/neu serum biochemistry was studied. Results: Age of the patients ranged from 25-75 years. Twenty-three cases (41.1%) were premenopausal while 33 cases (58.9%) postmenopausal. Forty-seven cases (83.9%) were of the infiltrating ductal carcinoma (NOS) type. Serum positivity for HER-2/neu was noted in 29 (51.8%) cases. Serum HER-2/neu levels showed a positive correlation with increase in tumour size, grade, stage of tumour and lymph node involvement. Serum HER- 2/neu positivity was seen in 20 (68.9%) IHC positive patients and 9 (33.3%) IHC negative patients, with a statistically significant correlation (p=0.005). Conclusion: Serum HER-2/neu levels directly correlate with prognostic factors like tumour size, grade, stage of the tumour and lymph node metastasis and can be used as a complimentary tool to tissue HER-2/neu immunohistochemistry.